Application of Law No. 16 of 2019 Concerning Minimum Age for Marriage Perspective of Effectiveness Theory of Lawrence Milton Friedman (Case Study in Sukosari Village, Jatiroto District, Lumajang Regency) - Elma Habibah Naila; Saliki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The regulation on the minimum age for marriage in Indonesia is a never-ending problem. Since the stipulation of Law No. 1 of 1974 until it was changed by Law No. 16 of 2019, many Indonesians do not comply with the regulations regarding the minimum age limit for marriage that has been set. In this regard, couples who do not obtain permission to marry from the state then choose to carry out marriages based on religious regulations, namely with a sirri contract. Such cases can be found in the village of Sukosari, as an area where the majority of the population marry early with sirri contracts. The problem is analyzed using an empirical juridical approach with the effectiveness theory of Lawrence M. Friedman. The results of this study state that the ineffectiveness of the minimum age limit for marriage is the local legal culture which makes early marriage with a sirri contract a habit, assuming that there is nothing more important than hastening marriage when it reaches the age of maturity. In the form of legal substance, the absence of direct sanctions against couples who do not register their marriage is the main factor in ignoring these regulations.